THE LEGAL ASPECTS AND URGENCY OF LEASE AGREEMENTS MADE BEFORE A NOTARY AND REGISTERED AT THE LAND OFFICE ACCORDING TO ARTICLE 127B OF THE REGULATION OF THE MINISTER OF AGRARIAN AFFAIRS AND SPATIAL PLANNING/NATIONAL LAND AGENCY NUMBER 16 OF 2021 - Syahira Sumantri, Nabila; Purba, Hasim; Suprayitno, Suprayitno (Penerbit Lafadz Jaya, 2025)
The lease agreement for land and buildings plays an important role in providing legal certainty and protection for the parties involved. In practice, however, such agreements are often not registered at the Land Office as specified in Article 127 B of the Regulation of the Minister of Agrarian Affairs and Spatial of the National Land Agency Number 16 of 2021. This leads to various legal issues that can affect certainty and legal protection for the parties. Based on this issue, this study formulates three main research questions: (1) What is the urgency of lease registration by the interested parties with the Land Office? (2) How is legal protection provided for tenants who register their lease objects at the Land Office under Article 127 B of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 16 of 2021? (3) What are the possible legal impacts, both disadvantages and advantages, of registering lease agreements with the Land Office as regulated by Article 127 B of the said regulation? This research employs a normative juridical method. This research approach also uses a conceptual approach (Conceptual Approach), the conceptual approach is intended